2020
DOI: 10.21203/rs.3.rs-29491/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Noninvasive KRAS mutation estimation in colorectal cancer using a deep learning method based on CT imaging

Abstract: Background: The detection of Kirsten rat sarcoma viral oncogene homolog ( KRAS )gene mutations in colorectal cancer (CRC) is key to the optimal design of individualized therapeutic strategies. The noninvasive prediction of the KRAS status in CRC is challenging. Deep learning (DL) in medical imaging has shown its high performance in diagnosis, classification, and prediction in recent years. In this paper, we investigated predictive performance by using a DL method with a residual neural network ( ResNet ) to es… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…According to the method of dividing points by sample as a threshold, it can be inferred that the value of the recall rate is gradually increasing, but it is not strictly increasing, because as the dividing point moves to the right, it seems that the positive example is divided into positive examples. The more and the accuracy rate is gradually decreasing, not strictly decreasing [43]. As the division point moves, the positive examples are judged as more positive examples, and the negative examples are judged as more negative examples.…”
Section: Conv1mentioning
confidence: 95%
“…According to the method of dividing points by sample as a threshold, it can be inferred that the value of the recall rate is gradually increasing, but it is not strictly increasing, because as the dividing point moves to the right, it seems that the positive example is divided into positive examples. The more and the accuracy rate is gradually decreasing, not strictly decreasing [43]. As the division point moves, the positive examples are judged as more positive examples, and the negative examples are judged as more negative examples.…”
Section: Conv1mentioning
confidence: 95%
“…However, these studies involved small sample sizes and lacked validation. Radiomics provides a variety of parameters for quantitative analysis, and these parameters have been widely used in cancer diagnosis, classi cation, and prediction 10 . A previous study demonstrated a signi cant correlation between a CT-based radiomics signature and KRAS/NRAS/BRAF mutations in CRC patients 11 .…”
Section: Introductionmentioning
confidence: 99%
“…In existing methods, two datasets are publicly accessible: NCT-CRC-HE-100K and Colorectal Histology based Ensemble Deep Neural Network to Tumor in images of Colorectal Histology, a framework using a classifier of CNN model and a generator of Cycle GAN [14][15][16][17]. Mask R-CNN and performance evaluation with different modern convolutional neural networks (CNN) as its feature extractor for polyp segmentation and detection and an ensemble method depending on the dataset of MICCAI polyp detection, (NCT) the National Center for Tumor diseases data sets, to classify the CRC histopathological images, the ResNet-50 model and transfer learning was used.…”
Section: Introductionmentioning
confidence: 99%